Newly identified 1.89 Ga mafic dyke swarm in the Archean Yilgarn Craton, Western Australia suggests a connection with India - Stark, J. Camilla; Wang, X.; Denyszyn, S.; Li, Z.; Rasmussen, Birger; Zi, Jianwei; Sheppard, Steve; Liu, Y. (Elsevier BV, 2017)
The Archean Yilgarn Craton in Western Australia is intruded by numerous mafic dykes of varying orientations, which are poorly exposed but discernible in aeromagnetic maps. Previous studies have identified two craton-wide dyke swarms, the 2408 Ma Widgiemooltha and the 1210 Ma Marnda Moorn Large Igneous Provinces (LIP), as well as limited occurrences of the 1075 Ma Warakurna LIP in the northern part of the craton. We report here a newly identified NW-trending mafic dyke swarm in southwestern Yilgarn Craton dated at 1888 ± 9 Ma with ID-TIMS U-Pb method on baddeleyite from a single dyke and at 1858 ± 54 Ma, 1881 ± 37 and 1911 ± 42 Ma with in situ SHRIMP U-Pb on baddeleyite from three dykes. Preliminary interpretation of aeromagnetic data indicates that the dykes form a linear swarm several hundred kilometers long, truncated by the Darling Fault in the west. This newly named Boonadgin dyke swarm is synchronous with post-orogenic extension and deposition of granular iron formations in the Earaheedy basin in the Capricorn Orogen and its emplacement may be associated with far field stresses. Emplacement of the dykes may also be related to initial stages of rifting and formation of the intracratonic Barren Basin in the Albany-Fraser Orogen, where the regional extensional setting prevailed for the following 300 million years. Recent studies and new paleomagnetic evidence raise the possibility that the dykes could be part of the coeval 1890 Ma Bastar-Cuddapah LIP in India. Globally, the Boonadgin dyke swarm is synchronous with a major orogenic episode and records of intracratonic mafic magmatism on many other Precambrian cratons.